Limites du systeme de collecte du maïs comme vivrier marchand dans les hauts plateaux de l'Ouest Cameroun - JEAN NOËL NGAPGUE (Cinq Continents, 2015)
Limits of the system of maize collection developed by traders in West Cameroon plateau . In the Western high plateau region of Cameroon, maize is a cash crop but the farmers do not understand the marketing system giving way to middlemen traders to benefit from the disorganisation of the maize trade to exploit the relationship between the farme rs and the market. This paper seeks to know whether maize trade through middlemen can help peasant farmers to adequately fight against poverty. Findings show that in spite of adequate maize production the trade through middlemen presents limitations. The middlemen attend only the periodic markets and those one located in accessible places. They buy maize in small quantities at very low prices and stock in small relay centres for short periods of time. These centres therefore function simply loading maize and cannot serve as veritable poles of economic development. Such are the handicaps in the commercialisation of maize which cannot contribute to the development of maize farming with attendant improvements to the living conditions of the farmers.